2012
DOI: 10.1542/peds.2011-3075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Honey on Nocturnal Cough and Sleep Quality: A Double-blind, Randomized, Placebo-Controlled Study

Abstract: OBJECTIVES: To compare the effects of a single nocturnal dose of 3 honey products (eucalyptus honey, citrus honey, or labiatae honey) to placebo (silan date extract) on nocturnal cough and difficulty sleeping associated with childhood upper respiratory tract infections (URIs). METHODS: A survey was administered to parents on 2 consecutive days, first on the day of presentation, when no medication had been given the previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 27 publications
3
87
1
8
Order By: Relevance
“…29 However, dark-honey-containing products show significant benefit in symptom relief and the AAP supports their use. [30][31][32] Our finding that there was no change in codeine prescribing patterns associated with the 2006 guidelines is in line with previous work showing that practice guidelines have limited impact on provider behavior owing to many factors, including awareness, familiarity, agreement, and self-efficacy. 33 However, there have been examples of successful, low-cost initiatives to reduce use of harmful medications.…”
Section: Figuresupporting
confidence: 87%
“…29 However, dark-honey-containing products show significant benefit in symptom relief and the AAP supports their use. [30][31][32] Our finding that there was no change in codeine prescribing patterns associated with the 2006 guidelines is in line with previous work showing that practice guidelines have limited impact on provider behavior owing to many factors, including awareness, familiarity, agreement, and self-efficacy. 33 However, there have been examples of successful, low-cost initiatives to reduce use of harmful medications.…”
Section: Figuresupporting
confidence: 87%
“…The primary endpoint subjective finding supports the long-held association described by common cold patients of VVR use and improved sleep. It cannot be determined from these data alone whether this is a result of symptom relief facilitating sleep (as has been suggested for cough relief [29]) or a direct effect on sleep. However, the active ingredients in VVR are not known to have a sedative effect.…”
Section: Discussionmentioning
confidence: 96%
“…In some trials, it has been shown that honey has some potential benefits with the common cold, nocturnal coughs, and sleep quality in children (4). In this case, his mother had given him two teaspoons of honey with his breakfast for coughing.…”
Section: Discussionmentioning
confidence: 99%